Plant Phenology as a Biomonitor for Climate Change in Germany A Modelling and Mapping Approach - Schmidt, Gunther; Schönrock, Simon; Schröder, Winfried (SpringerBriefs in Environmental Science, 2014)
The investigations refer to the development of plant phenology since the 1960s in Germany. Spatiotemporal trends were assessed by means of regression kriging. It could be shown that there already is a distinct shift of phenological onset towards the beginning of the year of up to two weeks. In future, a shift of up to one month was calculated till 2080. Moreover, a prolongation of the vegetation period of up to three weeks was found. The findings are relevant for the development of mitigation measures to prevent from environmental, agricultural and economic issues due to climate change.